Structure of a monomeric photosystem I core associated with iron-stress-induced-A proteins from Anabaena sp. PCC 7120 - Ryo Nagao; Koji Kato; Tasuku Hamaguchi; Yoshifumi Ueno; Naoki Tsuboshita; Shota Shimizu; Miyu Furutani; Shigeki Ehira; Yoshiki Nakajima; Keisuke Kawakami; Takehiro Suzuki; Naoshi Dohmae; et al. (Nature Communications, 2023)
IsiAs are unique light-harvesting complexes in cyanobacteria. Here, authors solved the structure of a PSI monomer associated with six IsiAs from Anabaena by cryo-EM, which provide insights into molecular diversity and functions of different IsiAs.